3.5k views
4 votes
12(1-x) = 36
what’s the equation

User Zaqwsx
by
5.1k points

2 Answers

3 votes
Answer:

-12x + 12 = 33
User Flyx
by
5.7k points
5 votes

Answer:

-12x + 12 = 32............................. the equation

Explanation:

to determine the equation in this 12(1-x) = 36 expression is quite simple, you only need to open the bracket .

solution

12(1-x) = 36

12 - 12x = 32

-12x + 12 = 32............................. the equation

we can further evaluate for the value of x

-12x = 32 - 12

-12x = 20

divide both sides by the coefficient of x which is -12

-12x = 20

-12x/-12 = 20/-12

x = -1.67

User Bert Huijben
by
5.7k points